(untitled) (Journal of the College of Basic Education, 2026)
The aim of this study was to determine the effect of time on the physical and chemical properties of earthworm fluid extracted from earthworm incubators. Earthworms, classified within the phylum Annelida ,class Clitellata, order Oligochaeta, were reared in 30 cm diameter plastic incubators. Twenty worms were placed in each incubator, and grated potato was added daily as their feed. Earthworm fluid was collected from the incubators every two weeks. The results indicated a variation in the nutrient content of the earthworm fluid during the incubation period. It was also shown that the pH value decreased slightly, becoming acidic, decreasing from 6.5 to 5.5. Electrical conductivity levels also fluctuated. The percentage in the worm fluid was 3.16 after two weeks of the experiment, 3.51 in the fourth week, and reached its highest point at 4.27 in the sixth week, before decreasing to 2.67 in the eighth week. The results showed a slight increase in phosphorus concentration, rising from 0.022 to 0.62 during the collection process. The sodium content increased from 1.98 to 2.65. The results also showed a significant increase in nitrogen concentration from 5.8 to 15.8. Similarly, potassium concentration gradually increased in the worm fluid over the weeks of collection, from 1.20 to 5.75. However,the organic matter content in the incubators decreased significantly from 40.01 to 5.41. Furthermore, using grated potatoes as earthworm feed improves the nutritional composition and quality of the worm fluid, making it a valuable source of essential nutrients for plant growth.